Randomised controlled trial comparing cost effectiveness of general practitioners and nurse practitioners in primary care - Venning, P (British Medical Journal, 2000)
OBJECTIVE: To compare the cost effectiveness of general practitioners and nurse practitioners as first point of contact in primary care. DESIGN: Multicentre randomised controlled trial of patients requesting an appointment the same day. SETTING: 20 general practices in England and Wales. PARTICIPANTS: 1716 patients were eligible for randomisation, of whom 1316 agreed to randomisation and 1303 subsequently attended the clinic. Data were available for analysis on 1292 patients (651 general practitioner consultations and 641 nurse practitioner consultations). MAIN OUTCOME MEASURES: Consultation process (length of consultation, examinations, prescriptions, referrals), patient satisfaction, health status, return clinic visits over two weeks, and costs. RESULTS: Nurse practitioner consultations were significantly longer than those of the general practitioners (11.57 v 7.28 min; adjusted difference 4.20, 95% confidence interval 2.98 to 5.41), and nurses carried out more tests (8.7% v 5.6% of patients; odds ratio 1.66, 95% confidence interval 1.04 to 2.66) and asked patients to return more often (37.2% v 24.8%; 1.93, 1.36 to 2.73). There was no significant difference in patterns of prescribing or health status outcome for the two groups. Patients were more satisfied with nurse practitioner consultations (mean score 4.40 v 4.24 for general practitioners; adjusted difference 0.18, 0.092 to 0.257). This difference remained after consultation length was controlled for. There was no significant difference in health service costs (nurse practitioner £18.11 v general practitioner £20.70; adjusted difference £2.33, −£1.62 to £6.28). CONCLUSIONS: The clinical care and health service costs of nurse practitioners and general practitioners were similar. If nurse practitioners were able to maintain the benefits while reducing their return consultation rate or shortening consultation times, they could be more cost effective than general practitioners.